2012
DOI: 10.1021/nl301917d
|View full text |Cite
|
Sign up to set email alerts
|

Exciton–Plasmon Interactions in Quantum Dot–Gold Nanoparticle Structures

Abstract: We present a self-assembly method to construct CdSe/ZnS quantum dot-gold nanoparticle complexes. This method allows us to form complexes with relatively good control of the composition and structure that can be used for detailed study of the exciton-plasmon interactions. We determine the contribution of the polarization-dependent near-field enhancement, which may enhance the absorption by nearly two orders of magnitude and that of the exciton coupling to plasmon modes, which modifies the exciton decay rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
122
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 24 publications
4
122
0
8
Order By: Relevance
“…On the theoretical side, classical and quantum calculations for a QE placed in the middle of the junction of a plasmonic dimer show that the hybrid structure undergoes dramatic changes in the absorption cross section as compared to individual components. [12][13][14][15]23 Thus, the electromagnetic coupling between the QE and the plasmonic nanoparticles has been tackled both theoretically and experimentally leading to the advanced understanding of the underlying phenomena. However, much less is known on the role of the direct electronic coupling between the QE and the plasmonic nanoparticle.…”
mentioning
confidence: 99%
“…On the theoretical side, classical and quantum calculations for a QE placed in the middle of the junction of a plasmonic dimer show that the hybrid structure undergoes dramatic changes in the absorption cross section as compared to individual components. [12][13][14][15]23 Thus, the electromagnetic coupling between the QE and the plasmonic nanoparticles has been tackled both theoretically and experimentally leading to the advanced understanding of the underlying phenomena. However, much less is known on the role of the direct electronic coupling between the QE and the plasmonic nanoparticle.…”
mentioning
confidence: 99%
“…An example of this plasmon-enhanced emission was shown by positioning CdSe/ZnS QD in the nanogap of a 80 nm AuNP dimer that supports strong plasmon resonance, which was realized through surface-bound DNA hybridization between QD and AuNPs. 31 Single object measurement showed that the emission- Photonic nanoarchitectures X Lan and Q Wang enhancement factor approached the peaked maximum when the incident EM field was parallel to the dimer axis ( Figure 1b). This is associated with the strong EM field enhancement, which originates from the occurrence of longitudinal-bonding plasmon mode.…”
Section: Introductionmentioning
confidence: 98%
“…We derive this parameter using a semi-classical approach, and show its dependence on the dielectric constants of the system and on the distance from the metallic layer. Recently there has been considerable interest on utilizing surface plasmons in metallic thin films to enhance internal quantum efficiency of luminescent materials [1][2][3][4][5][6][7][8][9][10][11][12] and light emitting diodes (LED). …”
mentioning
confidence: 99%
“…In this scenario, one needs to solve the following rate equations in order to calculate η: [3] d N p dt = N P pl − N P P bt [4] Using Eqs. 3-4, we have considered the following cases: Case III, where there are no phonon losses and Case IV, where phonon losses are present.…”
mentioning
confidence: 99%